THE USE OF PREDICTION STRATEGY TO ENHANCE STUDENTS’ READING COMPREHENSION ON ENGLISH RECOUNT TEXT - Aliah, Askyah; Syam , Ummi Khaerati; Mahmudah , Dzur Rif'ah (English Language Teaching Methodology, 2025)
This research aims to investigate wheterprediction strategies can improve students’ reading comprehension in English recount texts in terms of main ideas and conclusions. The research design used is a pre experimental design. Using a one-group pre- test post- test design. The one- group pre- test post-test design involves one group undergoing pre- test (O1), treatment (X), and then post- test (O2). The results of the research showed that the implementation of prediction strategies improved students’ reading comprehension in terms of main ideas and conclusion. The average score of the students’ post- test was 84.36, while the average score of the students’ pre- test was 43.32, indicating an improvement of 95%. The results of the homogeneity test showed that the data was homogeneous. These results support the hypothesis that the implementation of prediction strategies can improve students’ reading comprehension.